Conspiracy of Silence in Palliative Care : A Concept Analysis (2019)
ABSTRACT: Background and Aim: With chronic diseases on the rise, there is a growing demand for palliative care. The global landscape of the integration of palliative care into health‑care systems is incipient, which leads to a lack of social awareness of this reality and consequently, to communication failures, particularly a conspiracy of silence. The aim of this study was to analyze the concept of conspiracy of silence in palliative care. Materials and Methods: Walker and Avant method of concept analysis was used. Review and synthesis of literature supported the analysis process. Forty‑seven articles were analyzed. Results: Results showed that the conspiracy of silence in palliative care is a communication failure, typical of limited life expectancy prognosis, and involves patients, their families, and health‑care teams. Lack of autonomy, overburden, family malfunctioning and coping, and health‑care dehumanization are consequences of the conspiracy of silence in palliative care. Conclusions: The present study had found that scales to measure this concept as well as interventions that consider important factors in the communication process in palliative care identified in this analysis are needed.